2001
DOI: 10.2307/3061007
|View full text |Cite
|
Sign up to set email alerts
|

Nature Reserves: Do They Capture the Full Range of America's Biological Diversity?

Abstract: Less than 6% of the coterminous United States is in nature reserves. Assessment of the occurrence of nature reserves across ranges of elevation and soil productivity classes indicates that nature reserves are most frequently found at higher elevations and on less productive soils. The distribution of plants and animals suggests that the greatest number of species is found at lower elevations. A preliminary assessment of the occurrence of mapped land cover types indicates that ϳ60% of mapped cover types have Ͻ1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
337
1
5

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(361 citation statements)
references
References 10 publications
(13 reference statements)
18
337
1
5
Order By: Relevance
“…Many studies that have evaluated present protected areas revealed representation bias toward high altitude and less-productive soils (Pressey and Taffs 2001;Scott et al 2001a;Rouget et al 2003). The main reason was that protected areas tended to be concentrated on land that was too remote or unproductive to be important economically (Pressey 1994).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Many studies that have evaluated present protected areas revealed representation bias toward high altitude and less-productive soils (Pressey and Taffs 2001;Scott et al 2001a;Rouget et al 2003). The main reason was that protected areas tended to be concentrated on land that was too remote or unproductive to be important economically (Pressey 1994).…”
Section: Discussionmentioning
confidence: 97%
“…Throughout the world, there are many cases of protected areas being set aside without any clear picture of regional conservation priorities and, in some cases, set aside out of sheer expediency (Pressey 1994). A consequence of this ad hoc reservation is that present protected areas are seldom located in landscapes where the opportunity costs of reservation are high, namely areas suitable for agriculture, forestry, and urban development (Pressey et al 1996;Scott et al 2001a). More accountable use of limited conservation resources requires systematic conservation planning as well as reliable information on the effectiveness of established or proposed protected areas (Margules and Pressey 2000).…”
Section: Introductionmentioning
confidence: 98%
“…For most distance groups, hardwood forest was the dominant land cover type, comprising 40% of the total land area within the study area during 1999. The total amount of land under protection from development along the Mississippi Gulf Coast is nearly three times the current national average of \6% for the coterminous United States (Scott et al 2001). Bottomland hardwood forests, in particular, receive the greatest amount of protection (*50%) of all forest types.…”
Section: Conservation Status Of Forested Stopover Habitatmentioning
confidence: 99%
“…The world's existing reserve network is inadequate to conserve the full complement of biodiversity because there is not enough area in reserves (Rosenzweig 1995(Rosenzweig , 2001; taxonomic coverage and representation of the world's biomes in reserves is grossly uneven (Brooks et al 2004); and the land that is protected tends to be characterized by relatively low productivity (Scott et al 2001;Hansen & Rotella 2002;Huston 2005). To complicate matters further, many large protected areas that were once considered remote are experiencing pressures from human population growth just outside their borders (Miller & Hobbs 2002;Sanderson et al 2002;Huston 2005).…”
Section: Conservation Design In Human-dominated Landscapesmentioning
confidence: 99%